A Prospective Longitudinal Study of U.S. Children Unable to Achieve Open-Set Speech Recognition 5 Years After Cochlear Implantation. Issue 6 (July 2015) - Barnard, Jennifer M.; Fisher, Laurel M.; Johnson, Karen C.; Eisenberg, Laurie S.; Wang, Nae-Yuh; Quittner, Alexandra L.; Carson, Christine M.; Niparko, John K.
Abstract : Objective: To identify characteristics associated with the inability to progress to open-set speech recognition in children 5 years after cochlear implantation. Study Design: Prospective, longitudinal, and multidimensional assessment of auditory development for 5 years. Setting: Six tertiary cochlear implant (CI) referral centers in the United States. Patients: Children with severe-to-profound hearing loss who underwent implantation before age 5 years enrolled in the Childhood Development after Cochlear Implantation study, categorized by level of speech recognition ability. Intervention(s): Cochlear implantation before 5 years of age and annual assessment of emergent speech recognition skills. Main Outcome Measure(s): Progression to open-set speech recognition by 5 years after implantation. Results: Less functional hearing before implantation, older age at onset of amplification, lower maternal sensitivity to communication needs, minority status, and complicated perinatal history were associated with the inability to obtain open-set speech recognition by 5 years. Conclusion: Characteristics of a subpopulation of children with CIs associated with an inability to achieve open-set speech recognition after 5 years of CI experience were investigated. These data distinguish pediatric CI recipients at risk for poor auditory development and highlight areas for future interventions to enhance support of early implantation.